I'm at differentiation of algebraic functions. There's an example in the module that I couldn't quite get how it led to that.

$y=\frac {(x+1)^3}{x^2}$

It's solved by using a combination of quotient and power rules. I'll enumerate how it's solved.

$(1) y′= \frac{(x^2(3(x+1)^2))–(x+1)^32x}{x^4}$

$(2) y′= \frac{x(x+1)^2 (3x–2(x+1))}{x^4}$

$(3) y′= \frac {(x+1)^2 (3x-2x-2)}{x^3}$

$(4) y′= \frac {(x+1)^2 (x-2)}{x^3}$

How did $(2)$ came to be? Why was it done like that? I just can't wrap my head around it. It just looked like it skipped a couple steps (at least to me). Can anyone help me with this?

  • $\begingroup$ apply quotient and chain rule together $\endgroup$
    – abcdefu
    Aug 15 at 10:12
  • 3
    $\begingroup$ They simply factor out $x(x+1)^2$ from both terms. Think of it as a reverse of the distribution law $\endgroup$
    – Cathedral
    Aug 15 at 10:25
  • 1
    $\begingroup$ @Cathedral oh so is that why (x+1)^3 is now (x+1)? $\endgroup$
    – Hal
    Aug 15 at 10:28
  • 1
    $\begingroup$ @TobyMak thanks for the answer! It seems easier now that a lot has explained $\endgroup$
    – Hal
    Aug 15 at 10:51
  • 1
    $\begingroup$ @Cathedral My guess is that the "next step" Hal was expecting after (1) would be to completely expand the numerator. Which ends up with a cubic that needs factoring, so it's a more complicated approach. @ Hal: a takeaway lesson is that sometimes the factored form of an expression is better, and sometimes the expanded form is better. Life will be a bit easier if you take a step back and think about which is better for each particular instance. $\endgroup$
    – Teepeemm
    Aug 15 at 18:57

3 Answers 3


If it gets too messy, you can always use logarithmic differentiation. Take the natural logarithm of both sides to get:

$$\ln y = \ln((x+1)^3) - \ln(x^2)$$ $$\ln y = 3 \ln(x+1) - 2 \ln x$$

and so using the chain rule, we have that $\frac{d}{dx} (\ln y)$, where $y$ is a function of $x$), is $\frac{1}{y} \cdot y' = \frac{y'}{y}$:

$$\frac{y'}{y} = \frac{3}{x+1} - \frac{2}{x} = \frac{3x - 2(x+1)}{x(x+1)} = \frac{x-2}{x(x+1)}$$

so using what $y$ is, we have that:

$$y' = \frac{dy}{dx} = \frac{x-2}{x(x+1)} \frac{(x+1)^3}{x^2} = \frac{(x-2)(x+1)^2}{x^3}$$

  • 1
    $\begingroup$ If OP is just learning how to differentiate algebraic functions, I don't know that they've covered differentiating the natural logarithm and the chain rule, let alone logarithmic differentiation. $\endgroup$
    – Teepeemm
    Aug 15 at 18:49

Here is one way to solve it. Use the fact that the derivative of $(ax+b)^n=n(ax+b)^{n-1}(ax+b)'$. This just follows from the chain rule.

Rewrite the equation as $y=(x+1)^3x^{-2}$. Then apply the product rule. The product rule says $(f(x)g(x))'=f(x)g'(x)+g(x)f'(x)$.

Thus, we get $((x+1)^3x^{-2})'=((x+1)^3\cdot-2x^{-3})+3(x+1)^2x^{-2}$.

Writing this out in a clean way we get: $((x+1)^3x^{-2})'=\frac {-2(x+1)^3} {x^3}+\frac {3(x+1)^2} {x^2}=\frac {-2(x+1)^3+3x(x+1)^2} {x^3}$.

Now factor out $(x+1)^2$ to get $\frac {(x+1)^2(-2(x+1)+3x)} {x^3}=\frac {(x+1)^2(-2x-2+3x)} {x^3}=\frac {(x+1)^2(x-2)} {x^3}$


Before we start, let's recall the first derivative of a quotient:

Let: $$y(x)=\frac{u(x)}{v(x)}, v(x)\ne 0$$ then:


Apply for your case:

$$y(x)=\frac{(x+1)^3}{x^2}$$ then: $$y'(x)=\frac{[(x+1)^3]'x^2-(x+1)^3[x^2]'}{x^4}=\frac{3(x+1)^2x^2-2x(x+1)^3}{x^4}$$ now use the common factor $x(x+1)^2$ then: $$y'(x)=\frac{x(x+1)^2[3x-2(x+1)]}{x^4}=\frac{(x+1)^2(x-2)}{x^3}$$

  • $\begingroup$ @Teepeemm Thank you, i edited this answer. $\endgroup$
    – OnTheWay
    Aug 16 at 2:56

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.